Heavy Metal Accumulation in Medicinal plants and Risk assessment - Y. Pelikhovich; I. Begday; K. Kharin; T. Tsesar (Наука. Инновации. Технологии, 2022)
Introduction: Long-term monitoring of the quality of surface waters in a specific area reveals regional features of the formation of the chemical composition of natural waters and the ranges of quantitative characteristics of the studied compounds of pollutants. Materials and methods of the research: The work studies the long-term variability (2005 - 2019) of the content of dissolved forms of manganese and molybdenum compounds in the water of four rivers: Terek, Malka, Baksan, Cherek. The choice of these metal compounds is due to the assumption of their significant content in the rocks that make up the drainage basin of the Terek River and their active participation in geochemical processes. Determination of the content level of the dissolved forms of these compounds was carried out by the atomic absorption method using a spectrometer with electrothermal atomization “MGA-915M”. Excel was used for mathematical and statistical data processing. The results of the study and their discussion: The results of the analysis presented in Table 1 show that the range of fluctuations in the concentrations of the compounds of these metals in the studied objects and in the middle and lower reaches are different. This indicator is an important characteristic of the series and provides the first general idea of the difference in indicators within the population. The revealed levels of the content of heavy metal compounds (HM) in the water of rivers for the studied long-term period are illustrated by histograms. Conclusions: In the water of the Baksan, Terek, Malka, Cherek rivers for the period 2013- 2019, there is a tendency towards an increase in the level for the content of manganese compounds, both in the middle and in the lower reaches. Exceeding the maximum permissible concentrations of dissolved forms of manganese and molybdenum compounds is mainly associated with the peculiarities of the lithological structure of the catchment basins. Increased values of the content of molybdenum are observed in the water of the Baksan river in the middle course, which is explained by the location of the tailing dump of the mining and processing plant in the catchment area of the river.